2018
DOI: 10.1099/mic.0.000635
|View full text |Cite|
|
Sign up to set email alerts
|

Gene drive inhibition by the anti-CRISPR proteins AcrIIA2 and AcrIIA4 in Saccharomyces cerevisiae

Abstract: Given the widespread use and application of the clustered regularly interspaced short palindromic repeats (CRISPR)/Cas gene editing system across many fields, a major focus has been the development, engineering and discovery of molecular means to precisely control and regulate the enzymatic function of the Cas9 nuclease. To date, a variety of Cas9 variants and fusion assemblies have been proposed to provide temporally inducible and spatially controlled editing functions. The discovery of a new class of ‘anti-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 45 publications
3
95
0
1
Order By: Relevance
“…In fact, proof-of-concept CRISPR-based homing gene drives have recently been developed in several organisms including yeast (29)(30)(31)(32), flies (33)(34)(35)(36)(37)(38), mice (39), and two malaria vector species, Anopheles gambiae (40)(41)(42) and Anopheles stephensi (43).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, proof-of-concept CRISPR-based homing gene drives have recently been developed in several organisms including yeast (29)(30)(31)(32), flies (33)(34)(35)(36)(37)(38), mice (39), and two malaria vector species, Anopheles gambiae (40)(41)(42) and Anopheles stephensi (43).…”
Section: Introductionmentioning
confidence: 99%
“…A number of Acrs have been identified for type I [23,[25][26][27][28], type II [29][30][31][32] and type V [28,33] CRISPR-Cas systems. Acrs can be adapted to regulate CRISPR-Cas activities in bacteria [34], yeast [35] and mammalian cells [29,31,34,[36][37][38]. Biosensor [39] and synthetic circuits [40] can be devised based on Acr-coupled CRISPR-Cas systems.…”
Section: Inhibition Off-target Activitymentioning
confidence: 99%
“…A recent approach provided a more detailed mechanism of the AcrIIA2-mediated inhibition of spCas9, showing that AcrIIA2 as a DNA mimic interacts with the PAM recognition residues of Cas9, thereby preventing target dsDNA detection [79]. Basgall et al [80] demonstrated that AcrIIA2 and AcrIIA4 are able to inhibit the functional activity of Cas9 in vivo within haploid yeast and in an active gene-driven system, providing the first documented use of AcrIIA2 and AcrIIA4 to inhibit such a system. Furthermore, AcrIIA2 has been shown to exhibit temperature-dependent anti-CRISPR inhibitory activity, which may explain why AcrIIA2 can only partially inhibit spCas9 activity in E. coli and human cells [81].…”
Section: Type II Anti-crispr Proteinsmentioning
confidence: 99%